Written for the West: Reading Three Iranian Women’s Memoirs (American Journal of Islam and Society, 2008)
The burgeoning cannon of memoirs and fiction written by or about Iranianwomen has saturated the literary scene of post-9/11America. We have seenliterary works translated or mostly written by exiles that entice the curiouswestern reader with Orientalist tales ofMuslim women as veiled, unveiling,powerless victims, or brave escapees of an inherently oppressive patriarchy.The titles and contents of many of these works show that appealing to a specificpolitical climate and power structure is a key factor behind their production,dissemination, and consumption. Therefore, despite this literaryboom, it is not certain whether these books add anything to our knowledgeof Muslims or if, in fact, they actually obfuscate it.I read several such memoirs while drawing up the required reading listsfor the undergraduate courses that I teach at anAmerican liberal arts college.Working under the assumption that exposure to literary self-representation isan effective way of familiarizing students with contemporary Muslimwomen’s lives, I eventually chose three books written in English by threecontemporary Iranian women specifically for western audiences. In its ownparticular way, each one addresses gender and the experiences of women inMuslim societies: Azar Nafisi’s Reading Lolita in Tehran: A Memoir inBooks (Random House: 2003), Fatemeh Keshavarz’s Jasmine and Stars:Reading More Than Lolita in Tehran (University of North Carolina Press:2007), and Shirin Ebadi’s Iran Awakening: A Woman’s Journey to ReclaimHer Life and Country (Random House: 2007) ...